Teachers’ Materials Development, Lesson Planning, and Teaching Skills Readiness in Teaching English - Hidayah Nor; Nani Hizriani; Nur Laila Kadariyah (PANYONARA: Journal of English Education, 2022)
During online and offline teaching learning, teachers need to be ready and consider certain aspects in order to teach effectively and get the best results for the students. This research was aimed to know the English teachers’ readiness in terms of materials development, lesson planning, and teaching skills in online and offline teaching and learning. This study adopted embedded mixed research design that utilized closed-ended questionnaires and interview as instruments for data collection. There were 72 English teachers from Junior and Senior high schools (SMP, MTS, SMA, SMK, and MA) around South Kalimantan as the subject of the research. The result showed that most of the English teachers were ready in developing materials, lesson plan, and teaching skills. They were familiar with the types, the objectives, the principles and the stages in developing materials. In preparing lesson plan, they consider cognitive, affective, and psychomotor aspects, basic competencies, instructional media, character education, literacy 4 C's and HOTS skills activities, learning sources, and assessment. In applying teaching skills, the teachers did some adaptations and improvements by using a variation of online and offline applications in teaching.